Internalizing the Values of Tolerance and Religious Harmony Through Islamic Education Learning at SMA Muhammadiyah 1 Medan - Azhari, Abdul; Ranti, Sofvia; Amanda, Rakhel Qori (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
The objectives of this research include describing the process of internalizing the values of tolerance and religious harmony at SMA Muhammadiyah 1 North Sumatra through the think pair share strategy in Islamic Education learning. Analyzing the supporting and inhibiting factors for internalizing the values of tolerance and religious harmony at SMA Muhammadiyah 1 North Sumatra. The research uses qualitative research with a descriptive approach. Data collection techniques include observation, interviews and documentation. The data analysis technique uses the Miles and Huberman model. The results of this research show that the process of internalizing the values of tolerance and religious harmony at SMA Muhammadiyah 1 North Sumatra through the think pair share strategy in PAI learning includes: Learning planning: creating a syllabus, lesson plans, compiling materials, and preparing facilities and infrastructure. Implementation of learning: the teacher teaches, students practice, and the teacher provides feedback. Learning assessment: test, non-test, and observation. Supporting factors for internalizing the values of tolerance and religious harmony: teacher creativity, collaboration with the academic community. Factors inhibiting the internalization of the values of religious tolerance and harmony: unrestricted and unsupervised social media, lack of attention from parents and the surrounding environment. The conclusion is: The think pair share strategy is effective for internalizing the values of tolerance and religious harmony at SMA Muhammadiyah 1 North Sumatra. Teacher creativity and cooperation from the academic community are supporting factors, while unrestricted and unsupervised social media and lack of attention from parents and the surrounding environment are inhibiting factors.